Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015): International Scientific Conference, 31 August to 10 September 2015, Tomsk, Russia; [proceedings]; IOP Conference Series: Materials Science and Engineering (2016, 2016)
Title screen